Development of a Prone Team and Exploration of Staff Perceptions During COVID‐19. (2021) - Miguel, Karen; Snydeman, Colleen; Capasso, Virginia; Walsh, Mary Ann; Murphy, John; Wang, Xianghong Sean
Abstract : Objective: As intensive care unit bed capacity doubled because of COVID‐19 cases, nursing leaders created a prone team to support labor‐intensive prone positioning of patients with COVID‐related acute respiratory distress syndrome. The goal of the prone team was to reduce workload on intensive care teams, standardize the proning process, mitigate pressure injuries and turning‐related adverse events, and ensure prone team safety. Methods: Staff were trained using a hybrid learning model focused on prone‐positioning techniques, pressure injury prevention, and turning‐related adverse events. Results: No adverse events occurred to patients or members of the prone team. The prone team mitigated pressure injuries using prevention strategies. The prone team and intensive care unit staff were highly satisfied with their experience. Conclusion: The prone team provided support for critically ill patients, and team members reported feeling supported and empowered. Intensive care unit staff were highly satisfied with the prone team.